Gambaran Permasalahan Pemberian ASI pada 6 Bulan Pertama - Ridha Setiadewi Ridha (Jurnal Medika Hutama, 2023)
Background: Breastmilk is an essential liquid during infant early stage of life. The low coverage of breastfeeding is thought to be a threat to growth and development of infant, which will affect the quality of human resources. Methods: this study applied descriptive design with a cross sectional approach. There were 104 participants taking part in this study, who were selected using nonprobability sampling method with quota sampling type. The location of this research was conducted in Riau Province using an online survey of all mothers who have problems giving breastfeeding for the first six months, and mothers can access the internet to be able to fill out a questionnaire. Result: this study describes the majority of the participants were between the age of 26 and 35 (57,7%). While 78,8% of the participants held bachelor degree; most of participants were working mothers (51,9%). With 51% of the infants were female; most of the breasfeeding mothers in the Province of Riau come from the city of Pekanbaru (53,8%) and the more exclusive breastfeeding duration is six months (54,8%), the most common problem found during breastfeeding was breast engorgement 70,2%, while the least common problem experience was breast abscess (22,1%). Conclusion: the problem related to brestfeeding in the first six months period found in was breast engorgement while the problem to breastfeeding in the first six months period found in Riau provinde occured among infants age 0-2 months, which is the age where most problems with breastfeeding occur are influenced by various factors including physiologic increasesd milk production, maternal mental health and experiences of mothers in breastfeeding.